Traditional games of coastal Bengkulu and the formation of civic disposition: Exploring lickona’s essential moral values in elementary education - Atika Susanti; Kiki Amaliah; Pebrian Tarmizi; Nady Febri Ariffiando (Universitas Papua, 2026)
The decline in the practice of traditional games due to modernization has limited opportunities for students to experience character formation through culturally rooted activities. This study aims to explore the relevance of Bengkulu coastal traditional games in shaping elementary school students’ civic disposition and to examine their alignment with Lickona’s eleven essential moral values. The main contribution of this study is the development of a model that integrates local traditional games into formal and informal education as a medium for character and civic education. A systematic literature review method was employed by analyzing thirty research articles published between 2020 and 2025. The analysis shows that traditional games such as Cabur, Congkak, Sekejaran, Bakiak, Bekel, Ingkau, and Lompek Kodok reflect key moral values including responsibility, honesty, fairness, tolerance, wisdom, self-discipline, cooperation, empathy, courage, and democratic participation. The study proposes three integration models: intraclass learning, Profil Pelajar Pancasila projects, and extracurricular activities. These findings demonstrate that traditional games not only preserve cultural heritage but also function as effective pedagogical tools to internalize moral and civic values. It is concluded that Bengkulu coastal traditional games provide a strategic and innovative approach to support character education in elementary schools.